2013 IEEE Power &Amp; Energy Society General Meeting 2013
DOI: 10.1109/pesmg.2013.6672421
|View full text |Cite
|
Sign up to set email alerts
|

More insight into the effects of load cycles and electrothermal stress on HVDC extruded cable reliability in the prequalification test

Abstract: The long-term prequalification (PQ) test of HVDC extruded cable systems according to CIGRE Technical Brochure (TB) 496 consists of a one year long series of "24 hours" load cycles. The duration of this load cycle test relies on a design life of 40 years at constant rated voltage and on an IPM voltage-time characteristic, without any explicit consideration of thermal and synergistic electro-thermal aging effects related to load cycles. Here, as a sequel of a former investigation, a previously proposed method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Indeed: 1) a two-step temperature profile was set up throughout the LC period of the PQ test; thus, the transient electric fields and the loss-of-life fractions were strongly inaccurate; 2) an approximated version of the electrothermal life model (18) was employed; 3) one single cable different from those treated here was analyzed; 4) no sensitivity analysis was performed like that included below. For all of these reasons, the results in Table II differ quantitatively from those in [23], with larger differences in the loss-of-life fractions and lives between the inner and the outer insulation. Thus, it can be concluded that the new procedure proposed and applied here is essential for a sound life estimation of HVDC cables in the presence of load cycles.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Indeed: 1) a two-step temperature profile was set up throughout the LC period of the PQ test; thus, the transient electric fields and the loss-of-life fractions were strongly inaccurate; 2) an approximated version of the electrothermal life model (18) was employed; 3) one single cable different from those treated here was analyzed; 4) no sensitivity analysis was performed like that included below. For all of these reasons, the results in Table II differ quantitatively from those in [23], with larger differences in the loss-of-life fractions and lives between the inner and the outer insulation. Thus, it can be concluded that the new procedure proposed and applied here is essential for a sound life estimation of HVDC cables in the presence of load cycles.…”
Section: Discussionmentioning
confidence: 74%
“…An analysis similar to the present one was carried out in [23], but the approach was far less rigorous than here. Indeed: 1) a two-step temperature profile was set up throughout the LC period of the PQ test; thus, the transient electric fields and the loss-of-life fractions were strongly inaccurate; 2) an approximated version of the electrothermal life model (18) was employed; 3) one single cable different from those treated here was analyzed; 4) no sensitivity analysis was performed like that included below.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the power flow of a cable while still maintain a satisfied safety margin, dynamic thermal rating methods are proposed [8]- [12]. These methods calculate the maximum conductor operating temperature on the basis of instantaneous cable loading and environment conditions [13]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…Better modeling, more advanced grid infrastructure, and faster computation capabilities in the context of smart grid operations lead to the necessity of determining the real-time ratings of power cables [8], [12]. Also, current research shows that accurate real temperature transients can be used to determine the useful life of cables in service with dedicated life models [15], [16]. This is very important for electric utilities because it directly impacts their asset management strategy.…”
Section: Introductionmentioning
confidence: 99%